The Role of Corporations in the Protection of Human Rights During the Covid-19 Pandemic - Hijriani Hijriani; Rizki Ramadani; Muhammad Nadzirin Anshari Nur (Universitas Ahmad Dahlan, 2022)
Introduction to The Problem: The essential role of corporations in the economic growth of a country is often accompanied by violations of human rights. In handling COVID-19, there is a tendency to clash between the need to fulfill the right to health and economic recovery, which results in the marginalization of human rights. Corporations still have to take responsibility for respecting human rights because a number of human rights aspects from the perspective of workers are vulnerable to being violated. Purpose/Objective Study: This study addresses the question of what corporations' roles are in protecting and respecting human rights during the pandemic, as well as what steps corporations take to fulfill their human rights responsibilities.Design/Methodology/Approach: This study uses normative legal research methods by collecting primary data to support secondary data. Data was obtained through legislation, library materials, and comparisons of previous research.Findings: Corporations, like the state, bear the same responsibility for respecting and protecting human rights through a series of measurable steps. Corporate responsibility in responding to economic difficulties and the health crisis during the COVID-19 pandemic is carried out by making reasonable efforts to prevent and reduce the impact of COVID-19 on workers' rights, as well as developing internal policies and establishing operational guidelines for respecting human rights in the management of a company.Paper Type: Research Article